2017
DOI: 10.1101/205153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting the genetic loci of past evolution

Abstract: Repetitions in the mutations found to be responsible for independent evolution of similar phenotypes in various taxa have led some biologists to propose that for certain evolutionary changes the causal mutations are predictable. We examine here the nature of the predictions that have been made and their associated arguments. Predictions about the loci of past evolution are retrodictions, i.e. inferences about events that occurred in the past. They are not based on elaborate models and they derive mainly from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Marginal eyespots in many Nymphalidae are concentrically organized and serve as models for studies of development, as for example, in Bicyclus anynana, where they have been shown to be positively regulated by Wingless (Wnt) (Özsu et al, 2017). Wnt signaling delimits the boundaries of wing spots, as reviewed by Martin & Courtier-Orgogozo (2017), and is affected by heparin. Figure 8(Aiii-Diii) suggests that, even though the serial border spots of the tawny emperor are not as concentrically organized as in many other nymphalids, they are nevertheless homologous.…”
Section: Heliconiinaementioning
confidence: 99%
“…Marginal eyespots in many Nymphalidae are concentrically organized and serve as models for studies of development, as for example, in Bicyclus anynana, where they have been shown to be positively regulated by Wingless (Wnt) (Özsu et al, 2017). Wnt signaling delimits the boundaries of wing spots, as reviewed by Martin & Courtier-Orgogozo (2017), and is affected by heparin. Figure 8(Aiii-Diii) suggests that, even though the serial border spots of the tawny emperor are not as concentrically organized as in many other nymphalids, they are nevertheless homologous.…”
Section: Heliconiinaementioning
confidence: 99%